2012
DOI: 10.1074/jbc.m112.349142
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Truncated Form of the Endoplasmic Reticulum Chaperone Protein, σ1 Receptor, Promotes Mitochondrial Energy Depletion and Apoptosis

Abstract: Background: An ER-associated chaperone protein, 1 receptor ( 1 R), regulates ER/mitochondrial Ca 2ϩ mobilization through the IP 3 receptor. Results: We identify a novel short splicing variant of 1 R, termed 1 SR, and demonstrate its dominant negative function. Conclusion: 1 SR interferes with 1 R function in mitochondrial Ca 2ϩ mobilization and ATP production under ER stress conditions. Significance: In contrast to 1 R function, 1 SR has detrimental effects on cell survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
79
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 56 publications
8
79
0
Order By: Relevance
“…Why high doses ($100 mM) of s1R agonists are required on voltage-gated ion channel (Church and Fletcher, 1995;Lupardus et al, 2000;Zhang and Cuevas, 2002) compared with its high receptor affinity (McCann et al, 1994;Matsumoto, 2007;Su et al, 2010) is not clearly understood. This could be due to the influence of the cellular environment, such as s1R-binding partners, post-translational modifications, isoform variations in s1R (Shioda et al, 2012), or direct interaction with the VGCC independent of the s1R high-affinity binding site (Church and Fletcher, 1995;Tchedre et al, 2008). Although nonspecific effects by high-concentration s1R agonist cannot be ruled out, blockade of s1R agonist effects on I Ca supports our view that agonist action on I Ca represents a relevant specific interaction between s1R and I Ca .…”
Section: Discussionsupporting
confidence: 73%
“…Why high doses ($100 mM) of s1R agonists are required on voltage-gated ion channel (Church and Fletcher, 1995;Lupardus et al, 2000;Zhang and Cuevas, 2002) compared with its high receptor affinity (McCann et al, 1994;Matsumoto, 2007;Su et al, 2010) is not clearly understood. This could be due to the influence of the cellular environment, such as s1R-binding partners, post-translational modifications, isoform variations in s1R (Shioda et al, 2012), or direct interaction with the VGCC independent of the s1R high-affinity binding site (Church and Fletcher, 1995;Tchedre et al, 2008). Although nonspecific effects by high-concentration s1R agonist cannot be ruled out, blockade of s1R agonist effects on I Ca supports our view that agonist action on I Ca represents a relevant specific interaction between s1R and I Ca .…”
Section: Discussionsupporting
confidence: 73%
“…38 We recently reported that σ1R overexpression promotes Ca 2+ transport into the mitochondria and increases mitochondrial ATP production. 27 We also reported that SA4503 treatment of AngII-exposed cardiomyocytes promoted Ca 2+ transport into the mitochondria of neonatal rat cardiomyocytes but had weak effects on Ca 2+ release to the cytosol. 30 Although chronic treatment of OVX-PO rats with SA4503 rescued OVX-PO-induced impaired vascular relaxation in the present study, it had no effect on vascular constriction.…”
Section: Effect Of Chronic Sa4503 Treatment On Akt Phosphorylation Inmentioning
confidence: 75%
“…In immunoblotting with σ1R antibody, σ1 short receptor of 12 kDa, an deletion σ1R mutant, that we previously identified. 27 The levels of σ1 short receptor did not change under these conditions.…”
Section: Effect Of Chronic Sa4503 Treatment On Ovx-po-induced Impairementioning
confidence: 80%
“…PP1␥ siRNA (sense, 5Ј-CAUUCAGAAAGCUUCAAAUdTdT-3Ј; antisense, 5Ј-AUUUGAAGCUUUCUGAAUGdTdT-3Ј) and negative control siRNA were purchased from Sigma-Aldrich. Transfections were performed using 100 nM PP1␥ siRNA according to published methods (29).…”
mentioning
confidence: 99%
“…Neuro-2a cells were transfected with expression vectors using Lipofectamine 2000 (Invitrogen), and experiments were performed 48 h later as described previously (29). Primary cultures of mesencephalic neurons were established using methods described previously with slight modifications (30).…”
mentioning
confidence: 99%